Extracorporeal Membrane Oxygenation as a Bridge to Lung Transplant - Stokes, John W.; Gannon, Whitney D.; Bacchetta, Matthew (Seminars in Respiratory and Critical Care Medicine, 2021)
Extracorporeal membrane oxygenation (ECMO) is a cardiopulmonary technology capable of supporting cardiac and respiratory function in the presence of end-stage lung disease. Initial experiences using ECMO as a bridge to lung transplant (ECMO-BTLT) were characterized by high rates of ECMO-associated complications and poor posttransplant outcomes. More recently, ECMO-BTLT has garnered success in preserving patients' physiologic condition and candidacy prior to lung transplant due to technological advances and improved management. Despite recent growth, clinical practice surrounding use of ECMO-BTLT remains variable, with little data to inform optimal patient selection and management. Although many questions remain, the use of ECMO-BTLT has shown promising outcomes suggesting that ECMO-BTLT can be an effective strategy to ensure that complex and rapidly decompensating patients with end-stage lung disease can be safely transplanted with good outcomes. Further studies are needed to refine and inform practice patterns, management, and lung allocation in this high-risk and fragile patient population.
Keywords: bridge to lung transplant; severe respiratory failure; end-stage lung disease; extracorporeal membrane oxygenation; extracorporeal life support